Evaluating multi-state systems reliability with a new improved method - Yasser Lamalem; Soufiane Hamida; Yassine Tazouti; Oussama El Gannour; Khalid Housni; Bouchaib Cherradi (Institute of Advanced Engineering and Science, 2022)
The computation of network reliability for a system with many states is an NP-hard issue. Finding all the minimum path vectors (d-MPs) lower boundary points for each level d is one of the few approaches for computing such dependability. This research proposed enhancements to the technique described in Chen's